ANALISIS ILUSI FISKAL DI PROVINSI NTT - Sobang, Rafael U.L.; Molidya, Aldarine; Bolang, Rikhard C. Th. (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2025)
This study aims to analyze the existence of the fiscal illusion phenomenon in East Nusa Tenggara Province (NTT) and to examine the effect of transfer funds and local revenue (Pendapatan Asli Daerah or PAD) on regional expenditure. The research employs a quantitative descriptive method using secondary data from 22 regencies/cities in NTT for the period of 2020–2024. The analysis is conducted using panel data regression with the Fixed Effect Model (FEM) approach. The results show that the General Allocation Fund (DAU) has a significant negative effect on regional expenditure, indicating the presence of fiscal illusion—a condition where an increase in central government transfers is not followed by an increase in productive spending. Conversely, Local Revenue (PAD) and Revenue Sharing Funds (DBH) have a significant positive effect on regional expenditure, while the Special Allocation Fund (DAK) and Regional Loans have no significant effect. These findings indicate that the fiscal structure of NTT remains characterized by a high level of dependency on central government transfers, reflecting that regional fiscal independence has not been fully achieved.